The Teutonic crusade in Prussia: reconstruction of a medieval fortified settlement complex at Unisław. (12th June 2019) - Wiewióra, Marcin; Wasik, Bogusz; Molewski, Paweł; Badura, Monika; Maciejewska, Karolina; Makowiecki, Daniel; Moszczyński, Paweł; Misiewicz, Krzysztof; Małkowski, Wiesław; Bogacki, Miron; Tyszkowski, Sebastian
Abstract: Abstract : Archaeological investigations at Unisław in western Poland have revealed a previously unknown stronghold of the Teutonic Order—the first of its type discovered in Prussia. Comprising a timber-and-earth fortress erected on an older Slavic settlement, the complex functioned up to the AD 1320s, before being replaced by a masonry castle. This new evidence illuminates how such strongholds developed during the colonisation and formative years of the State of the Teutonic Order, and highlights the need for the reconsideration of assumptions concerning the associated architecture.